The Bible, The Koran and Islamic Rulers in The Work of V.I. Dahl (Eurasian Journal of Humanities and Social Sciences, 2023)
The article deals with the influence of the holy books of the Bible of the Koran on the writer's work. In such parables as Soleiman and the Owl”, “Soleman and the Crow”, “The Ram. The oriental tale is about kind, wise and just Islamic rulers”.